Effect of thermal conductivity of ceramic compact on the porous structures of foamed bodies via direct-foaming method. Issue 1 (2nd January 2020) - Shimamura, Akihiro; Fukushima, Manabu; Hotta, Mikinori; Kondo, Naoki
ABSTRACT: The effect of the thermal conductivity of ceramic compact on the porous structure of a foamed body formed by the direct foaming process was investigated. In order to change the thermal conductivity of the ceramic compact, three types of ceramic powder (alumina, mullite, and cordierite) with different particle sizes were used. These ceramic powders were mixed with powdered resol resin, which is a foamable thermoset resin used as both a foaming agent and binder for the ceramic powders. Ceramic compacts were prepared from the mixed starting ceramic and resol powders by press molding, and then characterized by thermal conductivity. The foamed bodies were produced from the ceramic compacts by heating to the resol foaming temperature to produce porous structures. The pore structures of the foamed bodies were strongly affected by differences in thermal conductivity in the ceramic compacts.